2020
DOI: 10.1017/s1355617720000478
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and Theory of Mind in Alzheimer’s Disease: A Meta-analysis

Abstract: Objective: A large literature now shows that Alzheimer’s disease (AD) disrupts a number of social cognitive abilities, including social perceptual function and theory of mind (ToM). However, less well understood is how the specific subcomponents of ToM as well as both the broader and specific subcomponents of empathic processing are affected. Method: The current study provides the first meta-analytic review of AD that focuses on both empathy and ToM as broad constructs, as well as their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 96 publications
(151 reference statements)
4
17
0
Order By: Relevance
“…This disconnection between the cognitive and affective subcomponents of empathy has been confirmed in several other neurological diseases. For example, in patients with Alzheimer's disease, there was a moderate-sized deficit in cognitive empathy/affective ToM, but no impairment in affective empathy (96). Patients with Parkinson's disease, compared to HCs, PD had significant impairment in cognitive empathy/affective ToM, but no group differences were identified in affective empathy (97).…”
Section: Discussionmentioning
confidence: 95%
“…This disconnection between the cognitive and affective subcomponents of empathy has been confirmed in several other neurological diseases. For example, in patients with Alzheimer's disease, there was a moderate-sized deficit in cognitive empathy/affective ToM, but no impairment in affective empathy (96). Patients with Parkinson's disease, compared to HCs, PD had significant impairment in cognitive empathy/affective ToM, but no group differences were identified in affective empathy (97).…”
Section: Discussionmentioning
confidence: 95%
“…Empathy and self-empathy abilities have been little researched in the field of AD. In general, as the disease progresses, it is possible to find a correlation between changes in both abilities and brain degeneration [ 84, 85 ]. Specifically, it is well-known that through the AD continuum there is a degeneration of the EC [ 46, 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, patients with AD typically have a reduced capacity to recognize others' emotions (Güntekin et al, 2019). Furthermore, evidence for this was found in a meta-analysis of studies of patients with AD that found strong evidence for a decrease in patients' abilities to identify the thoughts, feelings, and motivations of others, a process called cognitive empathy or theory of mind (Demichelis et al, 2020). On the other hand, patients with AD show relative preservation in their ability to experience emotions such as compassion and sympathy towards others, a process called emotional empathy (Demichelis et al, 2020).…”
Section: A Case For Examining the Utility Of Interpersonal Synchrony In Alzheimer's Disease And Related Dementiasmentioning
confidence: 99%
“…Furthermore, evidence for this was found in a meta-analysis of studies of patients with AD that found strong evidence for a decrease in patients' abilities to identify the thoughts, feelings, and motivations of others, a process called cognitive empathy or theory of mind (Demichelis et al, 2020). On the other hand, patients with AD show relative preservation in their ability to experience emotions such as compassion and sympathy towards others, a process called emotional empathy (Demichelis et al, 2020). The patients' decreased capacity to understand others' motivations and feelings could lead to misunderstandings with the caregiver and cause unnecessary stress for the patient and increased caregiver burden.…”
Section: A Case For Examining the Utility Of Interpersonal Synchrony In Alzheimer's Disease And Related Dementiasmentioning
confidence: 99%